The effect of temperature and headspace on the determination of ethanol in post-mortem blood specimens: A South African perspective - Southon, Bianca (My University, 2019)
The Forensic Chemistry Laboratories in South Africa have, between the year 2014 and 2017, endured a lot of media scrutiny surrounding a backlog of specimens for blood alcohol and toxicology analyses and the poor environmental and storage conditions in which these specimens are kept. Many studies have been performed on the stability of alcohol in blood, since environments are not standard, to gain a better understanding on whether the backlog issues significantly impact on the integrity of the blood-alcohol concentration (BAC) results by evaluation of conditions, especially variables such as temperature and headspace. The aim of this study was therefore, to assess the stability of ethanol concentrations in post-mortem blood specimens by evaluating temperature (room and refrigerator) and headspace (4mL and 8mL) variables at 3 months and 6 months respectively. Blood from 119 decedents was collected, analysed and subjected to the varied volumes and storage conditions. Blood alcohol was determined and quantified using a G1888 Headspace Auto sampler (Agilent Technologies®) coupled to a 6890N Agilent® Gas Chromatography instrument utilising a Flame Ionization Detector on an Agilent HP-Innowax® column. A general decrease in alcohol concentration was observed over a storage period of 6 months regardless of the storage temperature, whilst headspace was found to have no significant effect on the BAC results. It is, therefore, important that Forensic Pathologists, investigators and scientists are aware of factors such as temperature and headspace and consider them when interpreting blood alcohol results from a post-mortem environment.
Submitted in fulfilment of the requirements for the degree of Masters of Science in Medicine in the Health Science Faculty University of Witwatersrand Johannesburg 10 April 2019
Keywords: Alcohol, ethyl; Alcoholism; Ethanol as fuel; Temperature measurents